Analysis of Indonesia's Electrical Energy Security Based on Aspects of Availability, Accessibility, Acceptability, and Affordability - Ginanjar, Gigin; Lisapaly, Leonard (CV. Publikasi Indonesia, 2025)
The increasing demand for electrical energy in Indonesia, driven by rapid economic growth, necessitates a comprehensive evaluation of the country’s electrical energy security across four critical aspects: availability, accessibility, acceptability, and affordability. Despite significant expansion in power generation capacity, with coal-fired plants still dominating the energy mix, environmental concerns regarding emissions pose major challenges to sustainability. This study aims to analyze Indonesia’s electrical energy security by quantitatively assessing 20 key indicators from 2008 to 2023 and projecting trends to 2030 and 2045. Employing data normalization and a rhombus area graphical model, the research integrates multi-dimensional data to provide a holistic security index. Results reveal improvements in availability, accessibility, and affordability over time, but acceptability declines due to rising greenhouse gas emissions, underscoring the environmental trade-offs of fossil fuel reliance. The findings highlight the urgent need for policy and technological interventions such as expanding renewable energy, implementing Carbon Capture and Storage (CCS) technologies, and promoting electrification of industrial and transport sectors. This study offers crucial insights for policymakers and stakeholders to balance energy growth with environmental sustainability, guiding Indonesia towards a secure and cleaner energy future.